Hubungan Tingkat Depresi Dengan Gejala COVID-19 Pasca Isolasi Mandiri - Aswan Jhonet; Rolin Soraya; Tusy Triwahyuni; Devita Febriani Putri (Jurnal Ilmiah Kesehatan Sandi Husada, 2022)
Introduction: COVID-19 is a new disease caused by SARS-CoV-2 which was discovered in Wuhan, China in 2019 and then became a global pandemic. The COVID-19 pandemic contributed to an increase in anxiety, depression, and other stress symptoms, one of which is due to the severity of the symptoms caused during self-isolation. Depression can affect anyone regardless of education, ethnicity, age, income, or marital status, which impacts worsening the course of the disease. Aims: Find out the relationship of depression levels with post-self-isolation COVID-19 symptoms. Method: This type of research is quantitative with an analytical survey research design. Data collection uses interviews and BDI-II questionnaires. The bivariate analysis uses the Spearman correlation test. Result: A correlation value of 0.819, indicating a relationship between depression levels and symptoms in post-self-isolation COVID-19 patients. Conclusion: The relationship is meaningful between depression levels and post-self-isolation COVID-19 symptoms.